Implementasi Digital Marketing Pada UMKM di Kabupaten Klungkung dalam Meningkatkan Profit - Pramawati, I.D.A Tantri; Putri, Kompiang Martina Dinata; Mulyawan, Arya (Jurnal Pendidikan Ekonomi Undiksha, 2020)
Technology in the digital world and the internet has greatly contributed to changes in marketing activities, which were previously conventional (offline) strategies but have now changed to digital (online). Digital marketing makes it easier for their businesses in the marketing process for the products they sell.This study took place in Klungkung Regency, Bali Province. Descriptive qualitative method to adjust opinions between researchers and informants. Selection of this method because the analysis could not be in the form of numbers and more researchers describe all the phenomena that exist in the community clearly. This study using observation, interviews, documentation and sampling technique was purposive sampling with the object of research being the owners of SMEs in Klungkung Regency. The purpose of this research is to find out SMEs actors in understanding digital marketing; to determine the use of social networks by SMEs players as digital marketing media; to find out the effect of digital marketing on increasing commodity profits for SMEs.Results from this study is their interest in SMEs to use digital marketing in the marketing of SMEs products; Brand awareness generated by using digital marketing affects profits; separation of accounts online stores with their personal accounts, this is done so in a social media management can actively focus for promoting SMEs